A tough, biodegradable and water-resistant plastic alternative from coconut husk. (15th July 2022) - Leow, Yihao; Sequerah, Veronica; Tan, Ying Chuan; Yu, Yong; Peterson, Eric Charles; Jiang, Changyun; Zhang, Zheng; Yang, Le; Loh, Xian Jun; Kai, Dan
Abstract: Bioplastics from lignocellulosic biomass have gained great interests due to its renewable nature and biodegradability. However, poor mechanical performance and water stability limit their practical applications. Plastic resins are normally required to bond the biomass compounds. In this work, a high-performance bioplastic from coconut husk is developed via a simple top-down and resin-free approach; coconut husk fragments are directly processed into bioplastics through the partial removal of lignin, followed by hot-pressing. By optimization of delignification conditions, the generated bioplastics achieve a tensile Young's modulus of 2.1 ± 0.4 GPa and a tensile strength of 22.8 ± 4.4 MPa. More importantly, these bioplastics show excellent water stability (up to 28 days of soaking) and decent microbial biodegradability. Furthermore, the potential use of the bioplastics is demonstrated as solid planar substrates for miniaturized, disposable electrochemical biosensors. This work provides a promising and green approach to prepare strong, wet-stable, and biodegradable lignocellulosic bioplastic as a potential solution to replace petroleum-based plastics. Graphical abstract: Bioplastics derived from waste coconut husks are fabricated via a top-down approach of partial lignin removal and densification. The process improved the mechanical properties via extensive hydrogen bonding. The treated bioplastics are also stable in water and displayed better biodegradability. The bioplastics are demonstrated to be a suitable substrate for glucose biosensor. Image 1